The populist radical right: a reader - Mudde, Cas (Routledge, Taylor & Francis Group, 2017)
Introduction : The Populist Radical Right Today / Cas Mudde -- Interregnum or Endgame? : The Radical Right in the "Post-Fascist" Era / Roger Griffin -- Party Ideology / Elisabeth Carter -- Against the Current-Stemming the Tide : The Nostalgic Ideology of the Contemporary Radical Populist Right / Hans-Georg Betz and Carol Johnson -- A New Winning Formula? : The Programmatic Appeal of the Radical Right / Sarah L. De Lange -- The European Extreme-Right and Islam : New Directions? / José Pedro Zúquete -- European Integration and the Radical Right : Three Patterns of Opposition / Sofia Vasilopoulou -- Right-Wing Extremism in Post-War Europe / Klaus von Beyme -- New Populist Parties in Europe / Paul Taggart -- Modern European Democracies and Its Enemies : The Threat of the Extreme Right / Ami Pedahzur and Leonard Weinberg -- Racist Extremism in Central and Eastern Europe / Cas Mudde -- Conservative and Right-Wing Movements / Kathleen M. Blee and Kimberly A. Creasap -- The Rebirth of Charisma? : The Cases of Jean-Marie Le Pen and Vladimir Zhirinovsky / Roger Eatwell -- Extreme Right Activists : Recruitment and Experiences / Bert Klandermans -- Becoming a Racist : Women in Contemporary Ku Klux Klan and Neo-Nazi Groups / Kathleen Blee -- Electoral Sociology : Who Votes for the Extreme Right and Why and When? / Kai Arzheimer -- The Radical Right Gender Gap / Terri Givens -- The Silent Counter-Revolution: Hypotheses on the Emergence of Extreme Right-Wing Parties in Europe / Piero Ignazi -- The New Politics of Resentment : Radical Right-wing Populism in Western Europe / Hans-Georg Betz -- The Contemporary Radical Right : An Interpretative and Explanatory Framework / Herbert Kitschelt (in collaboration with A.J. McGann) -- The Radical Right in Postsocialist Central and Eastern Europe : Comparative Observations and Interpretations / Michael Minkenberg -- Ten Theories of the Extreme Right / Roger Eatwell -- The Populist Radical Right : A Pathological Normalcy / Cas Mudde -- The Radical Right in Public Office : Agenda-Setting and Policy Effects / Michael Minkenberg -- The Extreme-Right and Immigration Policy-Making : Measuring Direct and Indirect Effects / Martin A. Schain -- Contagious Parties : Anti-Immigration Parties and Their Impact On Other Parties' Immigration Stances in Contemporary Western Europe / Joost van Spanje -- Comparing Radical Right Parties in Government : Immigration and Integration Policies in Nine Countries (1996-2010) / Tjitske Akkerman -- Populism and Liberal Democracy : Populists in Government in Austria, Italy, Poland and Switzerland / Daniele Albertazzi and Sean Mueller -- Three Decades of Populist Radical Right Parties in Western Europe : So What? / Cas Mudde -- Patterns of Response to the Extreme Right in Western Europe / Jaap Van Donselaar -- Between Adaptation, Differentiation and Distinction : Extreme Right-Wing Parties Within Democratic Political Systems / Alexandre Dézé -- Reacting to the Radical Right : Lessons from Germany and Austria / David Art -- New Alliances : Why Mainstream Parties Govern With Radical Right-Wing Populist Parties / Sarah L. De Lange -- Conclusion : Studying Populist Radical Right Parties and Politics in the 21st Century / Cas Mudde
Literaturangaben
Keywords: Europe -- Politics and government -- 1989-; Westliche Welt; Aufsatzsammlung; Partei; Rechtspopulismus; Rechtsradikalismus; Europa